Care for people living with HIV in the time of COVID-19: scoping review - Lima, Lucas Vinícius de; Pavinati, Gabriel; Piran, Camila Moraes Garollo; Andrade, Rubia Laine de Paula; Oliveira, Magda Lúcia Félix de; Magnabosco, Gabriela Tavares (ABCS Health Sciences, 2023)
This study aimed to analyze the scientific productions involving the repercussions of the COVID-19 pandemic on the actions and health services offered to people living with HIV. To this end, a scoping review was carried out following the recommendations of the Joanna Briggs Institute and PRISMA-ScR. The search took place in March 2022 in seven databases and the gray literature, with the descriptors: pandemic, COVID-19, SARS-CoV-2, HIV, HIV infections, health strategies, and health services, combined with operators booleans “AND” and “OR”. Two researchers independently searched for the data sources. With the search, 1,032 publications were identified, of which 42 were included. Difficulties in accessing and linking to health services were evidenced, such as reduced service hours, scarcity of materials, and reduction or overload of human resources, which weakened the offer of actions to monitor treatment, dispensing of medicines, and clinical follow-up. On the other hand, digital care and follow-up systems were employed, in addition to the use of long-term medication dispensing methods, resorting to places close to the affected people or even in their homes. In short, it was possible to verify that, despite the negative effects of the pandemic on health actions and services, threatening the achievements of the last 40 years in confronting the HIV epidemic, promising strategies to provide comprehensive, proactive, and continuous care were implemented in times of COVID-19.